Studi Deskriptif Kualitas Layanan Pembelajaran Guru SLB Berkualifikasi Pendidikan Non-Pendidikan Luar Biasa - Haryani, Isti; Hermawan, Irwan; Radisic, Drinka (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to determine how the quality of teaching services of Special School (SLB) teachers is in designing learning for students. The study was motivated by the fact that many teachers still teach outside their area of expertise, particularly in Special Education Schools. The research method used in this study is qualitative research, employing in-depth interview techniques with research subjects. The research subjects were special school teachers at SLB Bina Bakti, South Jakarta, with data collected through semi-structured interviews, observations, and documentation. Data validity was ensured using source triangulation and method/technique triangulation. Data analysis employed an interactive model consisting of data collection, data condensation, data display, and conclusion drawing. The results of this study indicate that the quality of teaching services of teachers at SLB Bina Bakti remains low due to the high number of teachers with non-special education qualifications at the school. This situation affects several aspects: 1) In lesson planning for students with emotional and behavioral disorders, teachers are still lacking in preparation and determining the appropriate models and methods. This is because teachers continue to use lesson plans that do not align with the standards for teaching students with special needs established by the school itself. 2) In the implementation of learning, teachers are still lacking in providing appropriate learning treatments for students with special needs, such as adapting materials, using varied methods, utilizing adequate media, and maintaining conducive classroom management. 3) Evaluation is relatively effective, often using written tests adjusted to the students needs and guided by teachers in completing the questions or evaluation tests according to the students conditions. Thus, teachers face numerous challenges in teaching students with special needs.